Pengaruh pertumbuhan perusahaan, investment opportunity set, profitabilitas, ukuran perusahaan, risiko bisnis dan struktur aktiva, terhadap struktur modal pada perusahaan property & real estate yang terdaftar di bursa efek indonesiatahun 2011-2012 - Fitri Kasuarina; Rasuli '; Alfiati Silfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The study aims to determine the effect of the investment opportunity set (IOS), the company's growth, profitability, risk and asset structure of capital structure on property & real estate company listed on the Indonesia Stock Exchange in 2011-2012.The population in this study are all property and real estate companies listed on the Indonesian Stock Exchange (BEI) in the period 2011-2012. The sample used by the authors in this study was determined using purposive sampling technique. The number of property & real estate company listed on the Indonesia Stock Exchange in 2011 and 2012 is as much as 49 companies. Data were analyzed using multiple regression.The rate of growth the company has a positive and significant impact on the capital structure. Investment Opportunity Set (IOS) and a significant positive effect on capital structure. Risk does not have a significant effect on capital structure. ROA positive and significant impact on the capital structure. Size positive and significant impact on the capital structure. The structure of assets and a significant positive effect on capital structure. This means that the policy asset structure on property and real estate company is one of the factors that can affect the capital structure that needs to be considered when investing in the stock exchange.Keywords: Growth Company, Investment Opportunity Set (IOS), Risk, Profitability, Asset Structure, Capital Structure